The level of metabolic hormones in young people with arterial hypertension against the background of abdominal obesity - Ya. V. Polonskaya; E. V. Kashtanova; E. M. Stakhneva; V. S. Shramko; E. V. Sadovski; S. R. Ledovskikh; L. V. Shcherbakova; E. V. Garbuzova; A. D. Khudyakova; Yu. I. Ragino (Бюллетень сибирской медицины, 2023)
Aim. To study the level of metabolic hormones in young people with arterial hypertension (AH) against the background of abdominal obesity (AO).Materials and methods. The study included 498 people who were divided into two groups. The experimental group encompassed 250 people with AH, of which – 159 people had AO, the average systolic pressure – 141.9 ± 13.9 mm Hg, diastolic pressure – 95.6 ± 7.5 mm Hg. The control group included 248 people comparable to the experimental group by gender and age, of whom 104 people had AO, the average systolic pressure – 118.5 ± 9.8 mm Hg, diastolic pressure – 77.8 ± 7.4 mm Hg. The levels of amylin, C-peptide, ghrelin, glucose-dependent insulinotropic polypeptide (GIP), glucagon-like peptide-1 (GLP-1), glucagon, insulin, pancreatic polypeptide (PP), and peptide YY (PYY) were determined by the multiplex analysis. The level of glucose was determined by the enzymatic method. Statistical processing of the results was carried out using the SPSS 13.0 software.Results. Patients with AH had higher levels of amylin, C-peptide, and glucose and lower levels of PYY. There was no significant difference between the experimental group and the control group for the rest of the studied parameters. In the experimental group, the C-peptide, GLP-1, glucagon, and insulin levels were associated with AO. In the control group, the association of AO with the levels of C-peptide, insulin, and glucose was shown. The odds of AH in people under the age of 45 years were associated with a decrease in the level of PYY, a rise in the amylin levels, and an increase in waist circumference.Conclusion. Of the studied metabolic hormones, an increased level of amylin and reduced PYY can serve as potential biomarkers indicating high odds of developing AH in people under 45 years of age. AO is a factor that contributes to the development of AH at a young age.